2007
DOI: 10.1111/j.1365-2958.2007.06047.x
|View full text |Cite
|
Sign up to set email alerts
|

Acquisition of a bacterial RumA‐type tRNA(uracil‐54, C5)‐methyltransferase by Archaea through an ancient horizontal gene transfer

Abstract: Comparative genomic and phylogenetic analyses show that homologues of PAB0719 and PAB0760 occur only in a few Archaea, these genes having been acquired via a single horizontal gene transfer from a bacterial donor to the common ancestor of Thermococcales and Nanoarchaea. This transfer event was followed by a duplication event in Thermococcales leading to two closely related genes. None of the gene products of the two P. abyssi paralogues catalyses in vitro the formation of m 5 U in a P. abyssi rRNA fragment hom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
72
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(75 citation statements)
references
References 52 publications
3
72
0
Order By: Relevance
“…1A; Table 1). Likewise, when a tRNA transcript specific for Phe, Asp, or Ile, lacking modifications, was incubated with AdoMet and cell extracts from P. furiosus or P. abyssi, m 5 U was almost quantitatively formed at position 54 of the TC-loop (Constantinesco et al 1999;Urbonavicius et al 2008). Under the same experimental conditions, U54 in the tRNA Ile transcript was shown to be ''doubly'' modified into m 1 C when incubated with cell extracts from H. volcanii (Grosjean et al 1995).…”
Section: Discussionmentioning
confidence: 76%
See 3 more Smart Citations
“…1A; Table 1). Likewise, when a tRNA transcript specific for Phe, Asp, or Ile, lacking modifications, was incubated with AdoMet and cell extracts from P. furiosus or P. abyssi, m 5 U was almost quantitatively formed at position 54 of the TC-loop (Constantinesco et al 1999;Urbonavicius et al 2008). Under the same experimental conditions, U54 in the tRNA Ile transcript was shown to be ''doubly'' modified into m 1 C when incubated with cell extracts from H. volcanii (Grosjean et al 1995).…”
Section: Discussionmentioning
confidence: 76%
“…Under the same experimental conditions, U54 in the tRNA Ile transcript was shown to be ''doubly'' modified into m 1 C when incubated with cell extracts from H. volcanii (Grosjean et al 1995). The enzyme responsible for the formation of m 5 U54 in P. abyssi was recently identified as PAB_0719 (aTrmU54) (Urbonavicius et al 2008;Auxilien et al 2011). This protein is a member of the COG2265 SAM-dependent, Rossmannlike RNA m 5 U methyltransferase family.…”
Section: Discussionmentioning
confidence: 84%
See 2 more Smart Citations
“…Recently, it has been shown that homologs of the bacterial rumA gene, which encodes the enzyme for m 5 U1939 in Escherichia coli 23 rRNA, are present in Archaea, but only in the members of Thermococcales and Nanoarchaea. Moreover, the product of this rumA-type gene has in vitro AdoMet-dependent tRNA m 5 U54 activity (Urbonavicius et al 2008). Therefore, it is possible that most of the P. furiosus tRNAs contain m 5 U54, while a select few have C54, as is the case for higher eukaryotes (Sprinzl and Vassilenko 2005).…”
Section: Differences In the Pseudouridylation Activities Of Mj-pus10 mentioning
confidence: 99%